PEMBUATAN RANCANG BANGUN PRASARANA PUBLIK UNTUK PENGEMBANGAN ECO TOURISM BATU KATAK KECAMATAN BAHOROK – LANGKAT - Marwan Lubis; Luthfi Parinduri; Shalahuddin Alayubi Sitanggang (Jurnal Pengabdian Mitra Masyarakat, 2022)
Province of North Sumatra has tremendous potential of tourism. This tourism object can be enjoyed by tourists, both local and foreign. Some of the attractions of North Sumatra that can be visited are Lake Toba, Samosir Island, Sibolga Beach, Berastagi and Bahorok which is located in Langkat Regency. Another tourist destination included in the Gunung Leuser National Park area is Tangkahan. Tangkahan has a unique selling point because it is a habitat for Sumatran elephants. Another choice of place that is no less interesting and can be enjoyed by the beauty of the environment is the ecotourism of Batu Katak which is located in Batu Katak Hamlet, Batujongjong Village, Bahorok District, Langkat. In the tourism sector, two factor: benefits and satisfaction of tourist are related to Tourism Resource and Tourist Service. Tourist objects and attractions are everything that exists in a tourist destination area that has its own charm and is able to invite tourists to visit. To increase the number of local and foreign tourists in North Sumatra, the government of North Sumatra continues making more improvements to facilities of tourism destinations, including the development of human resources. Other infrastructure matters that are not yet complete are rest areas, clean toilets, prayer rooms, halal cuisine, and area pointers (maps, signs, and so on). The purpose of this research is to design public infrastructure that is needed for the development of eco-tourism Batu Frog. The infrastructure includes toilets, tourist interpretation boards, hand washing (sanitation) places, trash cans, and road/way signs. The infrastructure created must meet the requirements of Clean Health Safety Environmental Sustainability (CHSE). With this infrastructure, it is expected to provide better services for tourists so that the number of visits in North Sumatra continues to increase. The success of eco-tourism development in Batu Katak is also expected to increase the income and welfare of the surrounding community. The specific objectives of this research are 1) Designing environmentally friendly supporting infrastructure as an effort to improve services to tourists who meet CHSE requirements, and 2) Making Detailed Engineering Design (DED) or bestek of toilets, tourist interpretation boards, hand washing places. , trash cans and directional/road signs. The stages that will be carried out in this research are problem identification, setting research objectives, literature and field studies conducted by interview and direct observation. The next stage is data processing and designing the initial design proposal.